The efficacy of power sharing politics in Zimbabwe: Lessons from Malaysia - Zengeni, Knocks Tapiwa (College of Law, Government and International Studies, Universiti Utara Malaysia., 2010)
This paper looks at the changing political equation in Zimbabwe since the emergence of powerful opposition at the turn of the century. As a result new political players and entrepreneurs have entered the political market and in the process challenging the founding fathers of the nation. An unprecedented political and economic crisis added new complexities to the future of the country and political rules of the game. In this sense, a new political regime arose in the form of a power-sharing framework involving the main political players in 2008. So, what lessons can Zimbabwe learn from the Malaysian consociational arrangement? The central proposition of this paper is that Zimbabwe can learn a lot from Malaysia despite the apparent differing circumstances and dynamics between the two countries.